Application of Interactive Multimedia (MMI) Tutorial Model to Improve Student Learning Outcomes at State of Elementary School (SDN) 5 Karangpawitan in ARTS and Culture Learning - Anti Yulianti; Juntika Nurihsan; Iman Nasrulloh (Riviera Publishing, 2026)
This study aims to analyze the effectiveness of the application of interactive multimedia (MMI) tutorial model in improving student learning outcomes in Arts and Culture learning at SDN 5 Karangpawitan. The research problem stems from the low student learning outcomes caused by conventional, teacher-centered learning methods that fail to engage students optimally in visual and creative subjects. A quantitative approach with a quasi-experimental method using a nonequivalent control group design was employed. The research subjects consisted of 56 fifth-grade students divided into an experimental class (n=28) receiving the MMI tutorial model intervention and a control class (n=28) receiving conventional instruction. Data collection techniques included pretest and posttest tests and observation. Data analysis was carried out through normality tests (Kolmogorov-Smirnov), homogeneity tests (Levene), N-Gain tests, and independent sample t-tests. The results showed that the average N-Gain value of the experimental class was 0.56 (medium category), which was higher than the control class at 0.32 (low category). The average posttest score of the experimental class reached 82.40 compared to 72.10 for the control class. The t-test results showed a significance value of 0.000 (p < 0.05), indicating a significant difference between the two classes. Thus, the interactive multimedia tutorial model is effective in improving student learning outcomes in Arts and Culture learning at SDN 5 Karangpawitan.